analisis - Andika Prianto Manalu; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Nosocomial infections are very influential on the patient's overall health condition and can increase morbidity and mortality. However, the incidence of nosocomial infections is still high. The problem in this study is the lack of nurses' ability to prevent and control nosocomial infections. The purpose of this study was to determine and analyze the ability of nurses related to this and its determinants at the Royal Prima Hospital Medan. This type of research is qualitative research with an interactive approach. There were 7 informants as nurses, 7 room heads and 1 PPI team. Methods of Data Collection by means of, In-depth Interviews, Observation and Documentation Studies. The study was conducted from February to March 2019. The results showed that the ability of nurses in the prevention and control of nosocomial infections was not maximal in accordance with WHO regulations. Determinants in its implementation include nurse education, lama work, place of assignment, HR needs and support tools, comfort of supporting facilities, training / outreach, monitoring and evaluation and coordination between units. The conclusion of the study is that the ability of nurses in the prevention and control of nosocomial infections at RSU Royal Prima Medan is already well established but there are some obstacles in its implementation. Keywords: ability , prevention, control, nosocomial infection